Asymmetric Total Synthesis and Biological Evaluation of (+)-Cycloclavine - McCabe, Stephanie R.; Wipf, Peter (Synthesis, 2019)
The first total synthesis of natural (+)-cycloclavine uses a catalytic asymmetric cyclopropanation of allene, a regiospecific Pd-catalyzed enone formation, and two intramolecular Diels–Alder reactions for indole/indoline annulations. The binding properties of natural (+)- and unnatural (–)-cycloclavine on 16 CNS receptors revealed significant stereospecificity and unique binding profiles in comparison to LSD, psilocin, and DMT. Differential 5-HT affinities, as well as novel sigma-1 receptor properties bode well for potential therapeutic developments of clavine alkaloid scaffolds.
Keywords: clavine ergot alkaloids; enantioselective allene cyclopropanation; psychedelics; stereospecific GPCR binding; LSD; psilocin; DMT; 5-HTA; sigma-1 receptors